PENERAPAN MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN MEDIA EDUCAPLAY DI SEKOLAH DASAR - Febry Aldha, Diah; Idris, Muhamad; Budi Irawan, David (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the Game-Based Learning (GBL) model assisted by Educaplay media at SD Negeri 128 Palembang, particularly in the topic of the human respiratory system. The main issue addressed is the limited use of innovative learning media, which has contributed to students' difficulties in understanding abstract Science and Social Studies (IPAS) concepts. Using a qualitative descriptive method, data were collected through observations, interviews, and documentation. The findings indicate that the use of Educaplay within the GBL model significantly enhances students' engagement and enthusiasm in learning. This interactive media transforms the learning environment into a more enjoyable experience and facilitates the visualization of complex concepts. Although technical challenges, such as internet stability, were encountered, the implementation of this model proved effective in improving students' motivation and conceptual understanding at the elementary school level.